Geotechnical properties and applicability of bentonite-modified local soil as landfill and environmental sustainability liners - Zullyadini A. Rahaman (Tanjung Malim, 2023)
Geotechnical properties and applicability of bentonite-modified local soil as landfill and environmental sustainability liners by Zullyadini A. Rahaman